2015
DOI: 10.1007/s10208-015-9270-z
|View full text |Cite
|
Sign up to set email alerts
|

A Primal-Dual Formulation for Certifiable Computations in Schubert Calculus

Abstract: Formulating a Schubert problem as solutions to a system of equations in either Plücker space or local coordinates of a Schubert cell typically involves more equations than variables. We present a novel primal-dual formulation of any Schubert problem on a Grassmannian or flag manifold as a system of bilinear equations with the same number of equations as variables. This formulation enables numerical computations in the Schubert calculus to be certified using algorithms based on Smale's α-theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(31 citation statements)
references
References 30 publications
(53 reference statements)
0
31
0
Order By: Relevance
“…We first compare these formulations to the determinatal formulation of a particular Schubert variety. Next, we determine which of the two uses fewer added variables for each Schubert variety on a flag manifold in C 9 , and then compare their computational efficiency for solving three Schubert problems, including two from [8]. We almost always observe a gain in efficiency for the lifted formulation over the primal-dual formulation.…”
Section: Comparison With the Primal-dual Square Formulationmentioning
confidence: 96%
See 4 more Smart Citations
“…We first compare these formulations to the determinatal formulation of a particular Schubert variety. Next, we determine which of the two uses fewer added variables for each Schubert variety on a flag manifold in C 9 , and then compare their computational efficiency for solving three Schubert problems, including two from [8]. We almost always observe a gain in efficiency for the lifted formulation over the primal-dual formulation.…”
Section: Comparison With the Primal-dual Square Formulationmentioning
confidence: 96%
“…Even if redundant minors are eliminated, the number that remains will in general exceed |w|. This is discussed for Grassmannians in Section 1.3 of [8], where it is shown that after removing redundancy, |w| = 0, 1 or a 1 = 1, n−1 are the only cases for which this number of minors equals |w|. In Section 3.1 we present a typical example minimally requiring 17 minors, but where |w| = 4.…”
Section: Determinantal Formulation Of a Schubert Varietymentioning
confidence: 99%
See 3 more Smart Citations